11C‐acetate positron‐emission tomography/computed tomography imaging for detection of recurrent disease after radical prostatectomy or radiotherapy in patients with prostate cancer. (5th December 2016) - Esch, Lukas Hendrik; Fahlbusch, Melanie; Albers, Peter; Hautzel, Hubertus; Müller‐Mattheis, Volker
Abstract : Objectives: To evaluate, in a prospective study, the effectiveness of computed tomography (CT)‐matched 11C‐acetate (AC) positron‐emission tomography (PET) in patients with prostate cancer (PCa) who had prostate‐specific antigen (PSA) relapse after radical prostatectomy (RP) or radiotherapy (RT). Patients and Methods: In 103 relapsing patients after RP ( n = 97) or RT ( n = 6) AC‐PET images and CT scans were obtained. In patients with AC‐PET‐positive results with localized PCa recurrence, detected lesions were resected and histologically verified or, after local RT, followed‐up by PSA testing. Patients with distant disease on AC‐PET were treated with androgen deprivation/chemotherapy. Results: Of 103 patients, 42 were AC‐PET‐positive. PSA levels were <1.0, <2.0 and <4.0 ng/mL in six, 16 and 20 patients, respectively. In 25/42 patients AC‐PET suggested lymph node metastases: 16/25 patients underwent surgery (10/16 metastasis, 6/16 inflammation); 9/25 patients underwent RT of lymph node metastases, which was followed by decreasing PSA level. In 17/42 patients who had distant disease, systemic treatment was commenced. Combining patients who underwent surgery and those who underwent RT, 19/25 patients were true‐positive in terms of AC‐PET (positive predictive value 76%). In 5/19 patients, PSA level was <2.0 ng/mL, in 2/19 patients it was <1.0 ng/mL and in 14/19 patients it was 5.4–23.1 ng/mL. In AC‐PET‐positive patients after surgery or RT (without androgen deprivation), median (range) time to renewed PSA increase was 6 (5–9) months. Conclusions: Only a minority of patients with relapsing PCa appear to benefit from AC‐PET for guiding potential local treatment. False‐positive results show that factors other than tumour metabolism induce increased AC uptake. The time free of recurrence after local treatment was shorter than expected.